Low Temperature Embrittlement studies on Stainless Steel 304 LN TIG Welds. (2018) - Maruthi, G Dilip; Purushotham, N; Rashmi, R
Abstract: Austenitic stainless steel 304LN (SS 304LN) is widely used in nuclear industry. TIG welding is selected here to weld the stainless steel plates because it offers the possibility of producing high quality and porosity free welds. However, weld metal experiences hot cracks during welding of austenitic stainless steels. Due to this, austenitic stainless steel welds are designed to have 3-8% delta ferrite in the weld metal to avoid hot cracks during solidification. With the presence of delta ferrite, when these materials are exposed to elevated temperature (300 - 500°C) the weld transforms into embrittlement phases such as iron rich α and chromium rich α, G phase and M23 C6 . These embrittlement phases deteriorate the mechanical properties of the weld. In this study, an attempt is made to study the low temperature embrittlement on SS 304LN TIG Welds. The low temperature embrittlement behaviour on aged samples at (300, 350, 400°C) was evaluated for 10000 hours by mechanical property testing and micro structural examination. Mechanical testing involves Hardness test and Impact test. Delta ferrite measurement was done to see any transformation of delta ferrite. Fracture surfaces were characterized using SEM. Increase in hardness with increase in aging temperature and decrease in delta ferrite content at 350°C and 400 °C clearly indicate that aging temperature affects kinetics of transformation of delta ferrite. Scanning Electron Microscopy did not show any transformation of delta ferrite. It was found that aging treatment has a strong influence on impact toughness. Decreases in impact toughness value especially at sub – zero temperatures indicate kinetics of transformation of delta ferrite is affected by aging temperature during low temperature aging.